Impacts of Government Spending Shock on Vietnamese Macroeconomic Aggregate Variables: DSGE and SVAR Models - Vu, Giang; Nguyen, Trang; Duong, Thanh; Pham-Hi, Duc (Communications in Mathematics and Applications, 2016)
Our research studies the impacts of government expenditure on the economical aggregate variables of Vietnam’s economy such as GDP, household consumption, government revenue, etc., with the presence of Non-Ricardian consumers. Our pa- per argues that aggregate household consumption and output will rise in response to an increase in government expenditure. Firstly, we use a structural vector auto- regression (SVAR) model to estimate the effects of government spending shock and find that it generates a strong increase in output, but it generates a weak in- crease in consumption. Then, we develop an open economy Dynamic Stochastic General Equilibrium (DSGE) model with the presence of Non-Ricardian house- holds and find that the results of DSGE model are a little better than those of SVAR model. In particular, the response of aggregate household consumption is relatively strong after government spending shock due to the consumer behavior of Non-Ricardian households. The assumption about the presence of Non-Ricardian households in DSGE model makes it differ from the Real Business Cycle (RBC) model. In DSGE model, an increase in government expenditure will induce to an increase in household consumption. In contrast with RBC model, an increase in government expenditure will induce to decrease in household consumption.